WHEN BUREAUCRACY MATTERS FOR ORGANIZATIONAL PERFORMANCE: EXPLORING THE BENEFITS OF ADMINISTRATIVE INTENSITY IN BIG AND COMPLEX ORGANIZATIONS. (27th February 2017) - ANDREWS, RHYS; BOYNE, GEORGE; MOSTAFA, AHMED MOHAMMED SAYED
Abstract: Administrative intensity is arguably a major determinant of public service performance. Although a large administrative function might constitute a bureaucratic burden, it could also enable organizations to better coordinate key activities. In particular, administrative intensity may strengthen or weaken the performance effects of other key organizational characteristics, such as size and task complexity. To explore these ideas, we analyse the separate and combined effects of administrative intensity, organization size and task complexity on the research and educational performance of UK universities between 2005 and 2011. The statistical results suggest that administrative intensity has a performance pay‐off for big and complex organizations.